Breathing adaptations of males in tig gall flowers (Hymenoptera: Agaonidae) - Ramírez, William (1996)
Apocryptophagus and Sycophaga wasps (Sycophaginae, sensu Boucek 1989) develop in the syconia of Sycocarpus and Sycomorus figs. The syconia are foil of a liquid when the males eclose Crom their galIs. The males have terminal abdominal filaments that are extensions of the peritremes. These filament